2010
DOI: 10.1103/physrevb.82.224509
|View full text |Cite
|
Sign up to set email alerts
|

YBa2Cu3O7/La0.7Ca<

Abstract: Heteroepitaxially grown bilayers of ferromagnetic La0.7Ca0.3MnO3 (LCMO) on top of superconducting YBa2Cu3O7 (YBCO) thin films were investigated by focusing on electric transport properties as well as on magnetism and orbital occupation at the interface. Transport measurements on YBCO single layers and on YBCO/LCMO bilayers, with different YBCO thickness dY and constant LCMO thickness dL = 50 nm, show a significant reduction of the superconducting transition temperature Tc only for dY < 10 nm,with only a slight… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…Epitaxial LCMO and YBCO thin films were grown on (001) SrTiO 3 (STO) substrates by pulsed laser deposition (PLD) [14]. A commercially available LCMO target was ablated by a KrF laser (λ = 248nm) with a repetition rate of 2 Hz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epitaxial LCMO and YBCO thin films were grown on (001) SrTiO 3 (STO) substrates by pulsed laser deposition (PLD) [14]. A commercially available LCMO target was ablated by a KrF laser (λ = 248nm) with a repetition rate of 2 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Gota et al [11] found an unexpectedly high value for the sampling depth of the iron magnetic oxide Fe 3 O 4 of 4.5 nm, in comparison to the one known for metallic Fe in the range 1.7 -2.2 nm, while d ≈ 2nm was found both in Ta 2 O 5 at the O K-3 edge [9] and in LaFeO 3 at the Fe L 2,3 edge [12]. Recently, transition-metal oxides with the perovskite structure and their interfaces have been intensely investigated, especially using XAS techniques to probe their interfaces [13,14] because of their potential application in spintronic or superconducting devices. Surprisingly, experimental determination of electron sampling depths for many of these technologically-relevant oxides has yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been discussed in terms of a "dead layer" or a "depleted layer." In addition, it was shown with x-ray magnetic circular dichroism (XMCD) that the interfacial Cu ions acquire a ferromagnetic moment of about 0.2 μ B , which is antiparallel to the one of Mn [9,11,17,18]. Recent x-ray resonant magnetic reflectometry (XRMR) studies have demonstrated that these Cu moments reside in the interfacial CuO 2 planes [19].…”
Section: Introductionmentioning
confidence: 99%
“…The common perovskite-related structure and similar in-plane lattice parameters, together with recent improvements in film deposition techniques, enable the layer by layer controlled epitaxial growth of multilayers and superlattices (SLs) with very sharp interfaces 17,20 . Experiments on this kind of oxide SC/FM heterostructures revealed effects such as a change in the SC critical temperature, T C , related to the presence and thickness of the FM layers, and vice-versa 17,19 ; a SC related giant magneto-resistance in FM/SC/FM trilayers 21 ; the enhancement of T C by an external magnetic field 22,23 and even a SC induced modulation of the magnetic moment in the FM layers 24 . These observations provide encouraging evidence for a sizable interaction between the SC and FM order parameters in these cuprate/manganite multilayer systems.…”
mentioning
confidence: 99%
“…Driven by curiosity and encouraged by the potential for applications, researchers have also started to investigate heterostructures involving high-T C cuprate superconductors (HTSC) and ferromagnetic manganites [14][15][16][17][18][19] . The common perovskite-related structure and similar in-plane lattice parameters, together with recent improvements in film deposition techniques, enable the layer by layer controlled epitaxial growth of multilayers and superlattices (SLs) with very sharp interfaces 17,20 .…”
mentioning
confidence: 99%